2019
DOI: 10.1038/s41551-019-0456-6
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Immune-orthogonal orthologues of AAV capsids and of Cas9 circumvent the immune response to the administration of gene therapy

Abstract: In the version of this Article originally published, in the heading for Fig. 1g 'DNA-targeting CRISPR effectors (285)' , '285' should have read '284'. In Fig. 3b,c,e and f, the final x axis label, ' AAV5-SaCas9' in blue, for the first dose was incorrect; the correct label is ' AAV5-SpCas9'. These figures have now been corrected. In addition, the caption for Supplementary Fig. 2 stated that 89 Cas13a, b and c orthologs were used; the correct number is 84. In Supplementary Table 1 the Cpf1 and Cas13 sequences we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We conjectured that the prolonged expression via icRNAs could facilitate genome and especially epigenome targeting. However, this same feature of persistence could also aggravate immune responses in therapeutic settings as CRISPR systems are derived from prokaryotes (32)(33)(34). Thus, to enable compatibility between persistence of expression and immunogenicity, we sought first to develop a methodology to screen progressively deimmunized SpCas9 proteins by combinatorially mutating particularly immunogenic epitopes (35).…”
Section: Resultsmentioning
confidence: 99%
“…We conjectured that the prolonged expression via icRNAs could facilitate genome and especially epigenome targeting. However, this same feature of persistence could also aggravate immune responses in therapeutic settings as CRISPR systems are derived from prokaryotes (32)(33)(34). Thus, to enable compatibility between persistence of expression and immunogenicity, we sought first to develop a methodology to screen progressively deimmunized SpCas9 proteins by combinatorially mutating particularly immunogenic epitopes (35).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we show that strategies commonly used to minimize cellular immune responses (e.g., tissue-specific promoter, prednisolone immune suppression) are insufficient to bypass Cas9 immunity. Comprehensive approaches, including but not limited to the use of an immune-attenuated/immune-privileged Cas9 gene expression cassette, nonviral vector-mediated transient Cas9 gene expression, immune tolerance induction, more potent immune suppression, and pre-screening for Cas9 immunity, might be necessary in order to translate AAV CRISPR therapy to DMD patients 10 , 13 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…To address these concerns, researchers have explored different Cas9 orthologs and AAV serotypes based on sequence similarities and predicted binding strength to major histocompatibility complex (MHC) class I and class II molecules. While no ortholog or serotype has been found to completely evade immune recognition, Moreno et al identified three Cas9 orthologs, namely, SpCas9, SaCas9, and Campylobacter jejuni Cas9 (CjCas9), that showed robust editing efficiency and tolerated repeated administration with reduced immunogenic toxicity in mice immunized against AAV and Cas9 ( Moreno et al, 2019 ). However, pre-existing immunity against SpCas9 and SaCas9 in humans leaves CjCas9 as the only current option for repeated gene therapy in this cohort of patients.…”
Section: Tackling Limitations: Recent Advancements In Crispr/cas Systemmentioning
confidence: 99%